261 NAD(P)H OXIDASE-DEPENDENT REACTIVE OXYGEN SPECIES GENERATION MEDIATES AMADORI-INDUCED MATRIX ACCUMULATION IN RENAL CELLS. Issue 1 (1st January 2007) - Al-Shahrouri, H. Z.; Block, K.; Lee, D.; Gorin, Y.; Abboud, H. E.
Abstract : Diabetic nephropathy (DN) is the leading cause of chronic kidney disease in the United States. Renal hypertrophy and extracellular matrix (ECM) accumulation are prominent features of DN. Chronic hyperglycemia leads to the accumulation of nonenzymatic glycation proteins known as Amadori and advanced glycation end products. Glycated proteins represent a major mechanism by which hyperglycemia leads to diabetic renal disease. Oxidative stress has emerged as a critical pathogenic factor in the development of diabetic complications, including DN. Research in our laboratory finds novel NAD(P)H oxidases, highly expressed in the kidney, to be major sources of reactive oxygen species (ROS) in diabetes. The purpose of the study is to investigate the mechanisms by which Amadori alter the redox state to mediate matrix expansion in glomerular mesangial cells. Methods: NADPH-dependent superoxide generation was measured using lucigenin-enhanced chemiluminescence and intracellular ROS production was measured using the peroxide-sensetive fluorescent probe 2′, 7′-dichlorofluorescin diacetate (DCF). To study ECM production, the expression of fibronectin (FN) and collagen IV expression was assessed by Western blot analysis and immunofluorescence confocal microscopy. Summary: Amadori products and control albumin were prepared by incubating human serum albumin (HSA) in the presence or absence of glucose for 1 week. In mesangial cells, Amadori-HSA stimulates NADPH-dependent superoxide generation compared with control-HSA measured by lucigenin-enhanced chemiluminescence in a dose- and time-dependent manner. In addition, we show that exposure of mesangial cells to Amadori-HSA resulted in an increase in DCF fluorescence. Amadori-HSA induces FN and collagen IV expression in mesangial cells as detected by Western blot analysis. Pretreatment of the cells with diphenyleneoidonium (DPI), an inhibitor of NAD(P)H oxidase, markedly reduces Amadori-HSA-induced FN expression as assessed by immunofluorescence confocal microscopy. Conclusion: NAD(P)H-oxidase isoenzyme(s) are activated by Amadori, leading to matrix accumulation in mesangial cells. This may represent an important mechanism by which Amadori products contribute to the pathogenesis of DN.